Antioxidant Activity of Edible Bird’s Nest (Aerodramus fuciphagus) from Central Borneo, Indonesia - Sandi, Dita Ayulia Dwi; Susiani, Eka Fitri; Rahmatullah, Satrio Wibowo; Adnyana, I Ketut; Wikaningtyas, Pratiwi (Borneo Journal of Pharmacy, 2025)
Edible bird's nests (EBNs) from Aerodramus fuciphagus have been traditionally used in Asia for their various health benefits, including antioxidant properties. Previous studies have reported antioxidant activity in EBN water extracts using methods like ABTS and ORAC. However, the antioxidant activity can vary significantly depending on factors such as the source of EBN, extraction methods, and the specific assay used. This study aimed to comprehensively evaluate the antioxidant potential of EBN water extract using a range of in vitro assays. The antioxidant activity was assessed using four different methods: 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging, nitric oxide (NO) radical scavenging, ferric reducing antioxidant power (FRAP), and cupric reducing antioxidant capacity (CUPRAC). Results demonstrated that the EBN water extract exhibited moderate NO radical scavenging activity with an IC50 value of 116.86 μg/mL. While weak activity was observed in the DPPH assay, the FRAP and CUPRAC assays showed promising antioxidant potential with an ascorbic acid equivalent (AAE) of 4.567±0.30 and 3.487±0.095 μg AAE/mL, respectively. These findings suggest that the antioxidant activity of EBN water extract may be primarily attributed to its protein content. However, further investigations are warranted to elucidate the specific mechanisms of action and isolate the bioactive compounds responsible for the observed antioxidant effects. These findings have implications for the development of EBN-based functional foods, nutraceuticals, and cosmeceuticals with enhanced antioxidant properties.